Effect of fiber surface on flexural strength in carbon fabric reinforced epoxy composites - Brocks, Thatiane [UNESP]; Cioffi, Maria Odila Hilário [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP] (Elsevier, 2013)
The effect of carbon fiber surface characteristics on flexural properties of structural composites is studied in this work. Two types of intermediate modulus carbon fibers were used: T800HB and IM7. Results revealed that higher mechanical properties are linked with higher interfacial adhesion. Morphologies and chemical compositions of commercial carbon fibers (CF) were characterized by Fourier Transformed Infra Red (FTIR) and Scanning Electronic Microscopy (SEM). Comparing the results, the T800HB apparently has more roughness, since the IM7 seems to be recovered for a polymeric film. On other hand, the IM7 one shows higher interactivity with epoxy resin system Cycom 890 RTM. Composites produced with Resin Transfer Molding (RTM) were tested on a flexural trial. Interfacial adhesion difference was showed with SEM and Dynamic Mechanical Analyses (DMA), justifying the higher flexural behavior of composites made with IM7 fibers. © 2013 Elsevier B.V. All rights reserved.
Keywords: Flexural properties; Interfacial adhesion; Structural composites; Surface properties; Chemical compositions; Dynamic mechanical analysis (DMA); Epoxy resin system; Interfacial adhesions; Resin transfer moldings (RTM); Scanning electronic microscopy (SEM); Adhesion; Carbon fibers; Epoxy resins; Interfaces (materials); Mechanical properties; Resin transfer molding; Resins; Bending strength